Association Between Pretransplant Cancer and Survival in Kidney Transplant Recipients. Issue 10 (October 2017) - Dahle, Dag Olav; Grotmol, Tom; Leivestad, Torbjørn; Hartmann, Anders; Midtvedt, Karsten; Reisæter, Anna V.; Mjøen, Geir; Pihlstrøm, Hege K.; Næss, Hege; Holdaas, Hallvard
Abstract : Background: Kidney transplantation in recipients with a previous malignancy is often deferred 2 to 5 years after cancer treatment due to fear of cancer recurrence. In Norway, the required waiting period has been 1 year. Methods: We compared patient and graft survival of recipients with pretransplant cancer to the outcomes of matched recipients without such cancer (comparators) using Cox regression. Results: From 1963 to 2010, 377 (6.4%) of 5867 recipients had a pretransplant cancer. During a median follow-up of 6.8 years, 256 recipients died, 35 (13.7%) from recurrent cancer and 27 (10.5%) from de novo cancer. Uncensored and death-censored graft loss occurred in 263 and 46 recipients, respectively. All-cause mortality was similar as in comparators (hazard ratio [HR], 1.06; 95% confidence interval [CI], 0.93-1.20]; P = 0.40), death-censored graft loss was lower (HR, 0.63; 95% CI, 0.47-0.84; P = 0.002), and uncensored graft loss was similar (HR, 0.99; 95% CI, 0.87-1.12; P = 0.87). Cancer mortality was higher than in comparators (HR, 1.97; 95% CI, 1.51-2.56; P < 0.001), particularly during the first 5 years of follow-up (HR, 3.44; 95% CI, 2.36-5.03; P < 0.01). Waiting period was not associated with recurrent cancer mortality or all-cause mortality (both P > 0.45). Results were similar within cancer subgroups, with most data in patients with a history of kidney cancer, prostate cancer, urothelial cancer, and skin squamous cell carcinoma. Conclusions: Kidney transplant recipients with a pretransplant cancer had a similar overall patient and graft survival as recipients without such cancer. Cancer mortality was increased, particularly during the first 5 years after transplantation. A short waiting period was not associated with mortality. Abstract : Kidney transplant recipients with a previous malignancy show a similar overall patient and graft survival compared to the recipients without a previous malignancy and a short waiting period (1 year) before transplantation is not associated with recurrent cancer mortality or all-cause mortality. Supplemental digital content is available in the text.